Use of intravenous immunoglobulin in chronic lymphocytic leukemia. A brief review. - Dicato, M; Chapel, H; Gamm, H; Lee, M; Ries, F; Marichal, S; Wirth, C; Griffith, H; Brennan, V (1991)
Chronic lymphocytic leukemia (CLL) is a disorder with multiple defects leading to an increased susceptibility to infection. Hypogammaglobulinemia is present in about 20% to 70% of patients with CLL. Intravenous immunoglobulin (IVIG) supplementation (400 mg/kg body weight every 3 weeks) prevented bacterial infections in these patients. An ongoing study is being conducted to compare doses of 250 mg/kg/mo with those of 500 mg/kg/mo in 36 patients included so far. As of this writing, the rate of infection in the two treatment groups was not significantly different, and no substantial loss of protection against bacterial infection was found in the lower-dose group. It seems likely that the lower dose is almost as effective as the standard therapy. If this is so, cost savings would be substantial.